2003
DOI: 10.1002/jcc.10227
|View full text |Cite
|
Sign up to set email alerts
|

Polarized basis sets of Slater‐type orbitals: H to Ne atoms

Abstract: We present three Slater-type atomic orbital (STO) valence basis (VB) sets for the first and second row atoms, referred to as the VB1, VB2, and VB3 bases. The smallest VB1 basis has the following structure: [3, 1] for the H and He atoms, [5, 1] for Li and Be, and [5, 3, 1] for the B to Ne series. For the VB2 and VB3 bases, both the number of shells and the number of functions per shell are successively increased by one with respect to VB1. With the exception of the H and Li atoms, the exponents for the VB1 base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 58 publications
3
78
0
1
Order By: Relevance
“…In this calculation, bound electron orbitals are described by the Slater type basis (STO) of triple-zeta quality (abbreviated as VB2 in Ref. [22]). Our zero-energy quantum defects were determined by matching the R-matrix, evaluated at 10 meV, to the Coulomb functions at distances beyond the boundary radius.…”
Section: Hehmentioning
confidence: 99%
“…In this calculation, bound electron orbitals are described by the Slater type basis (STO) of triple-zeta quality (abbreviated as VB2 in Ref. [22]). Our zero-energy quantum defects were determined by matching the R-matrix, evaluated at 10 meV, to the Coulomb functions at distances beyond the boundary radius.…”
Section: Hehmentioning
confidence: 99%
“…As in the search of the VB1 basis set, 15 for H and Li we have taken as a main reference the corresponding homonuclear diatomics. Furthermore, we have found that, in Li and Be, the extensions significantly affect the energies in molecules containing these atoms, i.e.…”
Section: Basis Set Extensionsmentioning
confidence: 99%
“…In this work we present a procedure for improving the degree of fulfillment of the electrostatic theorem and apply it to the improvement of the previously reported VB1 15 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study was limited to molecules with atoms of the first two rows of the periodic table because, at present, STO basis sets including polarization are only available for them. 25 All the calculations in this work have been made in the RHF framework, using experimental equilibrium geometries, with the VB1 Slater basis sets. 25 The calculation of the integrals was carried out with our own package for STO molecular integrals (SMILES).…”
Section: Analytic Representation Of the Atomic Densitiesmentioning
confidence: 99%